The Development of a Conceptual Change-Oriented E-Book in Environmental Science - Yuli Febrianti; Ivoni Susanti; Reny Dwi Riastuti; Rohmah Juliana; Ajeng Linggani (Jurnal Penelitian Pendidikan IPA, 2025)
Environmental science e-books that focus on conceptual change are educational resources that offer firsthand knowledge and complement environmental science lectures. This study aims to describe the design of the e-book, the responses of the validators, and the students' responses after the e-book was used as teaching material. The type of research conducted was Research and Development (R&D) with modifications to the Dick and Carey model, which includes three stages, namely the planning stage, the development stage, and the implementation stage. The development procedures included problem identification, data collection, e-book design, design validation, e-book revision, and product testing. The concept change-oriented environmental science e-book was designed per the format of a textbook consisting of four components: the book's exterior, the front part of the textbook, the content part, and the back part. This e-book is valid, practical, and effective, making it suitable as an independent learning resource for students. The linguistic validation results show that this e-book is valid with a score of 0.75. In a small group trial, this e-book was rated practical and effective with a percentage of 95.05%. In a large group trial, this e-book was also rated practical and effective with a percentage of 95.89%.